Acciones simpliciales del grupo modular de superficies de tipo infinito - Morales Jiménez, Israel (Universidad Michoacana de San Nicolas de Hidalgo, 2020)
The main contributions of this doctoral thesis are: 1. Alexander's method for infinite-type surfaces. For any infinite-type surface S possibly with non-empty boundary, there exist a collection τ of essential curves and arcs in S such that if h : S → S is a homeomorphism which preserves the isotopy class of the elements in Γ then h is isotopic (relative to the boundary of S) to the identity. 2. Topological rigidity of the curve complex. Every simplicial isomorphism between curve complexes of infinite-type surfaces is induced by a homeomorphism. 3. The automorphisms group of the curve complex. For every infinite-type surface S, the simplicial automorphisms group of the curve complex associated to S is isomorphic to the extended mapping class group of S, that is, Aut (C(S)) = Mod*(S). 4. The Hooper, Thurston and Veech construction. Let S be an infinite-type surface. Then there exist a pair of multicurves α and β whose union fills S, and there exist a flat structure τ on S such that the Dehn twists Tα and Tβ around the multicurves α and β, respectively, are a ne automorphisms of the flat surface M := (S; Γ). 5. Loxodromic big mapping classes. Let S be an infinite-type surface and p be a marked point in S. Then there exists an uncountable collection of elements in the group Mod(S; p) with loxodromic action on the loop graph of S. Moreover, every element of this collection does not preserve any finite-type subsurface of S.

Los principales resultados de esta tesis de doctorado son: 1. Método de Alexander para superficies de tipo infinito. Para toda superficie de tipo infinito S posiblemente con frontera no vacía, existe una colección Γ de curvas y arcos esenciales en S tal que si un homemorfismo h : S → S fija las clases de isotopia de los elementos en Γ entonces h es isotópico (relativo a la frontera de S) a la identidad. 2. Rigidez topológica del complejo de curvas. Todo isomorfismo simplicial entre grafos de curvas de superficies de tipo infinito está inducido por un homeomorfismo. 3. El grupo de automorfismos simpliciales del complejo de curvas. Para toda superficie S de tipo infinito, el grupo de automorifsmos simpliciales del complejo de curvas asociado a S es isomorfo al grupo modular extendido de S, es decir, Aut (C(S)) = Mod *(S). 4. Construcción de Hooper, Thurston y Veech. Sea S una superficie de tipo infinito. Entonces existe un par de multicurvas α y β y cuya unión llena la superficie S, y existe una estructura plana τ en S tales que los giros de Dehn Tα y Tβ a lo largo de las multicurvas α y β, respectivamente, actúan por automorfismo afines en la superficie plana M := (S; τ). 5. Elementos loxodrómicos. Sea S una superficie de tipo infinito y p un punto marcado en S. Entonces existe una colección no numerable de elementos en el grupo Mod(S; p) con acción loxodrómica en el grafo de lazos asociado a S. Más aún, los elementos de esta colección son homeomorfismos que no preservan ninguna subsuperficie de S de tipo finito.
Instituto de Física y Matemáticas. Facultad de Ciencias Físico Matemáticas. Unidad Morelia del Instituto de Matemáticas de la UNAM. Posgrado Conjunto de Doctorado en Ciencias Matemáticas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2633; info:eu-repo/classification/cti/1; IFM-D-2020-0465; Homeomorfismo; Complejo de curvas; Grafo de lazos